2009
DOI: 10.1016/j.chemgeo.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Spherulite crystallization induces Fe-redox redistribution in silicic melt

Abstract: Rhyolitic obsidians from Krafla volcano, Iceland, record the interaction between mobile hydrous species liberated during crystal growth and the reduction of ferric iron in the silicate melt. We performed synchrotron µ-FTIR and µ-XANES measurements along a transect extending from a spherulite into optically distinct colorless and brown glass zones. Measurements show that the colorless glass is enriched in OH groups and depleted in ferric iron, while the brown glass shows the opposite relationship. The color shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
(70 reference statements)
2
11
0
Order By: Relevance
“…If true, then our estimated spherulite nucleation temperatures of ~600-700 °C are equivalent to undercoolings of 300-400 °C, values similar to those determined in comparable experiments. Furthermore, quartz and alkali feldspar were experimentally estimated to grow at rates of 0.1-6 mm hr -1 , which are largely consistent with our estimates (Swanson, 1977;Baker and Freda, 2001;Castro et al, 2009). The cooling rate estimates determined independently from both techniques described herein can be interpreted to provide a firstorder constraint on the longevity of a largevolume prehistoric lava.…”
Section: Spherulite Geospeedometrysupporting
confidence: 54%
See 1 more Smart Citation
“…If true, then our estimated spherulite nucleation temperatures of ~600-700 °C are equivalent to undercoolings of 300-400 °C, values similar to those determined in comparable experiments. Furthermore, quartz and alkali feldspar were experimentally estimated to grow at rates of 0.1-6 mm hr -1 , which are largely consistent with our estimates (Swanson, 1977;Baker and Freda, 2001;Castro et al, 2009). The cooling rate estimates determined independently from both techniques described herein can be interpreted to provide a firstorder constraint on the longevity of a largevolume prehistoric lava.…”
Section: Spherulite Geospeedometrysupporting
confidence: 54%
“…Past experimental studies have examined how felsic minerals crystallize from melt in response to variable degrees of undercooling (Fenn, 1977;Swanson, 1977;Baker and Freda, 2001;Castro et al, 2009). Spherulites were the stable form in experiments that experienced large undercoolings ranging from 100 to 400 °C.…”
Section: Spherulite Geospeedometrymentioning
confidence: 98%
“…The uncertainties in oxygen isotope geothermometry limit ΔT estimates to sizable ranges. The estimates are consistent with experiments that performed spherulite growth at ΔT ranging from 100 to 400°C [Lofgren, 1974;Fenn, 1977;Kirkpatrick et al, 1979;Baker and Freda, 2001;Castro et al, 2009]. The Δ 18 O Qtz-Kfs temperature estimates are also comparable with constraints inferred from advection-diffusion modeling of incompatible constituent profiles surrounding spherulites in the same sample from Pitchstone Plateau [Befus et al, 2015].…”
Section: Discussionsupporting
confidence: 84%
“…The new estimate for spherulite growth is similar to the slower growth rates determined from experiments but is largely similar to results from advection‐diffusion modeling [ Fenn , ; Swanson , ; Baker and Freda , ; Castro et al , ; Arzilli et al , ; Befus et al , ]. Much of the discrepancy between the new rates and the faster rates determined from past experiments is simply a result of dissimilar materials.…”
Section: Discussionmentioning
confidence: 99%
“…Watkins et al (2009) argue that spherulite growth is lim ited by diffusivity of OH -, which is 10 -6 mm 2 /s in obsidian, and because thermal diffusivity is orders of magnitude higher, latent heat is con ducted away well before temperature can rise. However, theoretical spherulite growth times reported by Castro et al (2008) are shorter than those of Watkins et al (2009) and are verified by experimentally grown spherulites (Castro et al, 2009) on June 1, 2015 geosphere.gsapubs.org Downloaded from Secondary structures of ignimbrites is a limiting growth factor in nonporous obsid ian, it is less likely to constrain growth in partly permeable tuffs. Lastly, Watkins et al's (2009) analysis ignores scale effects, as is shown next.…”
Section: New Observationsmentioning
confidence: 53%